Pesantren dan Pemberdayaan Civil Society (Studi Kasus Pondok Pesantren Bayt Al-Hikmah Pasuruan) - Mukhammad Hasbi (Magister’s Program in Islamic Education Postgraduate Program, Universitas Annuqayah Sumenep, 2022)
Pesantren are recognized as the roots of civil society in Indonesia, because of their institutional and sociological role. Bayt Al-Hikmah as one of the pesantren plays this role comprehensively. This research will reveal: (1) the efforts of the Pesantren Bayt Al-Hikmah in strengthening the empowerment of civil society in the fields of education, da'wah, economics, politics and socio-culture, (2) the strategy of the Pesantren Bayt Al-Hikmah in carrying out the role of empowering civil society. As field research, researchers use civil society theory by collecting data through observation, interviews and documentation. Analysis of the data was carried out in two stages, namely the data collection stage and after the data was collected. The conclusions obtained are as follows. First, the efforts made by Bayt Al-Hikmah include educational and community activities at the same time. Educational activities take the form of a combination of Salaf and modern education, as well as religion for the community. Social activities are carried out by empowering (a) the economy through the Ummart mini market, Lazis, (b) politics through education and participation in politics based on pesantren values, (c) social and cultural activities carried out with various cultural activities. Second, the approach taken includes identifying problems, mapping service areas, identifying and classifying needs, identifying and mapping problems, studying the history of regional development, finding potential, analyzing problems and potential, choosing solutions and solving problems. These various approaches are carried out so that the efforts made are effective and right on target so as to achieve the expected goals.